2014
DOI: 10.3109/0284186x.2014.975369
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumors in Sweden: Data from a population-based registry 1999–2012

Abstract: background. The Swedish brain tumor registry has, since it was launched in 1999, provided significant amounts of data on histopathological diagnoses and on important aspects of surgical and medical management of these patients. The purpose is mainly quality control, but also as a resource for research. Methods. Three Swedish healthcare regions, constituting 40% of the Swedish population, have had an almost complete registration. The following parameters are registered: diagnosis according to SNOMED/WHO classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 14 publications
6
36
0
Order By: Relevance
“…While some studies reported gradually improved outcome with increasing extent of resection, only gross total resection may be associated with improved outcome. 34,35 RT has been standard of care for glioblastoma for decades, roughly doubling survival. 17,36 Standard dose is 60 Gy in 1.8-2 Gy fractions; 50 Gy in 1.8 Gy fractions improved survival relative to best supportive care in patients 70 years or older with good KPS.…”
Section: Glioblastoma Idh-wildtype -Who Grade IVmentioning
confidence: 99%
“…While some studies reported gradually improved outcome with increasing extent of resection, only gross total resection may be associated with improved outcome. 34,35 RT has been standard of care for glioblastoma for decades, roughly doubling survival. 17,36 Standard dose is 60 Gy in 1.8-2 Gy fractions; 50 Gy in 1.8 Gy fractions improved survival relative to best supportive care in patients 70 years or older with good KPS.…”
Section: Glioblastoma Idh-wildtype -Who Grade IVmentioning
confidence: 99%
“…Other national brain tumor registries, such as the Central Brain Tumor Registry of the United States [21] or the Austrian Brain Tumour Registry [22], have also reported high completeness of patients, although this has not been verified by comparing to a gold standard population as in this study. Regional brain tumor registries in France [23] and Sweden [24] have also reported high completeness.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate for patients with glioblastomas has improved with combined chemoradiotherapy, but still most patients are not long-term survivors [2]. Curative treatment is rare due to the infiltrative growth of the tumor [3].…”
Section: Introductionmentioning
confidence: 99%